West Meets East: New Concepts and Theories - Barkema, Harry G.; Chen, Xiao-Ping; George, Gerard; Luo, Yadong; Tsui, Anne S. (Academy of Management Journal, 2015)
Management scholarship has grown tremendously over the past 60 years. Most of our paradigms originated from North America in the 1950s to the 1980s, inspired by the empirical phenomena and cultural, philosophical, and research traditions of the time. Here following, we highlight the contextual differences between the East and the West in terms of institutions, philosophies, and cultural values and how they are manifest in contemporary management practices. Inspired by theory development in management studies over time, we offer insights into the conditions facilitating new theories, and how these might apply to emergent theories from the East. We discuss the contributions of the six papers included in this special research forum as exemplars of integrating Eastern concepts and contexts to enrich existing management theories. We highlight the difficulty with testing Eastern constructs as distinct from Western ones by discussing the properties of equivalence, salience, and infusion in constructs. We provide directions for future research and encourage an agentic view to creating new theories and paradigms.